Wpływ wieloletnich ram finansowych 2021–2027 Unii Europejskiej na zarządzanie rozwojem regionalnym w Polsce - Michalewska-Pawlak, Małgorzata (Polityka i Społeczeństwo, 2020)
The purpose of this paper is to analyze the impact of the European Union’s multiannual financial framework 2021–2027 on regional governance in Poland. The article is based on results of the research in the area of multilevel governance of the EU in the context of regional development. In particular, it aims to explore the influence of strategic and financial arrangements which might determine the processes of regional governance in Poland. The paper shows the key proposals elaborated by the European Commission and their potential consequences for the Polish regions. The final section of the paper describes how a new mechanism in the area of the rule of law as part of the conditionality rule can limit the access to the European Structural and Investment Funds for Polish regions. The paper has been elaborated using the following two methods: 1) institutional analysis of the key EU law regulations in the area of multiannual financial framework and regional policy; 2) case study. The article also implements up-to-date scholarly findings included in available scientific literature. The added value of the article is that the subject in question is yet to be discussed extensively by researchers.